The Impact of Information Systems Investment on Bank Performance in Ghana - Ankrah, Ebenezer (Advances in Social Sciences Research Journal, 2015)
The advancement of technology is a necessity of the current era. Businesses need to adopt and embrace new technologies to provide excellent business operations and services to their customers. This study looks at the impact of information systems investment on bank performance in Ghana. The major objectives are; (1) to determine the types of technology that the banks invest in (2) to find out the level of IS investment in the banks and (3) to determine the relationship between IS investments and bank’s performance. The following hypothesis was proposed and tested statistically “Information systems investment has a positive relationship with bank performance”. This study adopted the survey methodology. Taking into account the purpose of the study and the research hypothesis, this study is comfortably placed within a scientific epistemology of logical positivism. The cases investigated were local banks and foreign banks. The six banks used were named Bank A, Bank B, Bank C, Bank D, Bank E and Bank F respectively for the sake of anonymity. The population for the study was the strategic staff from the six banks all selected at their Head Offices in Greater Accra Region. The findings revealed that, there has been a high rate of investment in the past three years made by the various banks. The findings also revealed that both the foreign banks and the local banks asserted to the fact that, market share, profitability and ROA increases as IS investments are employed in the industry. Subjecting the hypothesis to statistical test also showed that, information systems investment has a positive relationship with bank performance. This study would help bank managers to recognize the importance of information systems investment and its use to gain competitive advantage and increase profit margins.